Considering the Power of Ahl Madinah Malik Bin Anas Ijma as an Islamic Legal Source - Nasruddin Yusuf; Faradila Hasan (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2020)
Ijmak Ahl Madinah became the method used in performing legal istinbath which was held by Imam Malik and was challenged by other scholars. Most of the other scholars consider this kind of ijmak, not ijmak but only an agreement for a region in the form of individual ijtihad which does not bind all the Muslims. Imam Malik considers the consent of ahl al-Madinah as an Ijma which has a specific value from the city of Medina itself. Imam Malik holds the ijma model as his source of law because it is considered to have continuity of authority with the main source, the qath'iy Qur'an wh the valid hadiths. This is different from the ijma that comes from the results of ijtihad, so it can be categorized as' urf which applies in the area of Medina and this cannot be said to be ijma.